Perbedaan Analisis Sefalometri Skeletal Sebelum dan Sesudah Perawatan Alat Myofunctional pada Pasien Maloklusi Dentoskeletal Kelas II Divisi I dalam Masa Pertumbuhan dengan Metode Steiner - Nugroho Ahmad Riyadi (Majalah Sainstekes, 2017)
The aim of orthodontics treatment is normalization of teeth position in three planes, using various orthodontics appliance to reach the chepalometric standar and normal occlusion. Orthodontic treatment for dentoskeletal class II division 1 malocclusion in growing patients using myofunctional appliance may correct anteroposterior planes of mandibula. This study was a descriptive retrospective analytic study to look at the success of Orthodontic treatment for dentoskeletal class II division 1 in growing patients with myofunctional appliance using chepalometrics analysis Steiner value. The sample used in this study is chepalogram radiographic from patient with dentoskeletal class II division 1 malocclusion in growing patients before and after using myofunctional appliance in PPDGS orthodontics Clinic of Padjadjaran University. Statistic analysis were performed with pair t-test and Wilcoxon. Based on this study, it is concluded that orthodontic treatment with myofunctional appliance such as activator and twin block in growing patient with dentoskeletal class II division 1 malocclusion shows significant changes and compatibility with the normal criteria.